Nikkei farmer on the Nebraska plains: a memoir - Kano, Hisanori (Plains histories, 2010)
"The memoir of Japanese-born Hisanori Kano, who immigrated to the United States in 1916 to learn and apply American agricultural practices on the Nebraska Plains. Ordained as an Episcopal minister and interned during WWII, Kano's memoir reveals how he adapted to a changing American culture and landscape"--Provided by publisher